E-COMMERCE APPLICATION DEVELOPMENT WITH SECURE PAYMENT METHOD INTEGRATION - Bekti Utomo; Kristiurman Jaya Mendrofa; Loso Judijanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research discusses the development of e-commerce applications with the integration of secure payment methods. The focus of this literature is to analyze the various approaches and technologies used to ensure secure financial transactions in e-commerce platforms. In the current digital era, payment security is an important factor that influences user trust and comfort. Through a study of various literature sources and previous research, we found that encryption technology, tokenization, and compliance with industry standards such as PCI-DSS (Payment Card Industry Data Security Standard) play a key role in preventing fraud and protecting customer data. Additionally, diversification of payment methods to include credit/debit cards, e- wallets, and bank transfers, not only enhances security but also provides more flexibility for users. This research also highlights the importance of regular evaluations and audits to keep systems up-to-date with the latest threats. The conclusion of this study confirms that the integration of secure payment methods not only increases the level of customer trust and loyalty but also becomes a critical business strategy for the long- term sustainability of e-commerce platforms.